2000
DOI: 10.2105/ajph.90.9.1372
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for emergency contraception: variability in hospital care of rape victims

Abstract: There is growing concern that rape victims are not provided with emergency contraceptives in many hospital emergency rooms, particularly in Catholic hospitals. In a small pilot study, we examined policies and practices relating to providing information, prescriptions, and pregnancy prophylaxis in emergency rooms. We held structured telephone interviews with emergency department personnel in 58 large urban hospitals, including 28 Catholic hospitals, from across the United States. Our results showed that some Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Espey and colleagues' (2009) survey of hospitals in a state with a mandated emergency contraception law found that only 52% of the responding emergency departments routinely provide emergency contraception to sexual assault patients. To date, no studies have found systematic differences in the provision of emergency contraception as a function of victim or assault characteristics, but Catholic hospitals are significantly less likely to provide emergency contraception (Smugar, Spina, & Merz, 2000).…”
Section: Victims' Experiences With the Medical Systemmentioning
confidence: 99%
“…Espey and colleagues' (2009) survey of hospitals in a state with a mandated emergency contraception law found that only 52% of the responding emergency departments routinely provide emergency contraception to sexual assault patients. To date, no studies have found systematic differences in the provision of emergency contraception as a function of victim or assault characteristics, but Catholic hospitals are significantly less likely to provide emergency contraception (Smugar, Spina, & Merz, 2000).…”
Section: Victims' Experiences With the Medical Systemmentioning
confidence: 99%
“…The American Medical Association (1995) and the American College of Obstetricians and Gynecologists (1998) recommend emergency contraception for victims at risk for pregnancy, but only 21% to 43% of sexual assault victims who need emergency contraception actually receive it (Amey & Bishai, 2002;Campbell, 2005Campbell, , 2006Campbell & Bybee, 1997;. To date, no studies have found systematic differences in the provision of emergency contraception as a function of victim or assault characteristics, but hospitals affiliated with the Catholic church are significantly less likely to provide emergency contraception (Campbell & Bybee, 1997;Smugar, Spina, & Merz, 2000).…”
Section: Victims' Help-seeking Experiencesmentioning
confidence: 99%
“…The American Medical Association (1995) and the American College of Obstetricians and Gynecologists (1998) recommend emergency contraception for victims at risk for pregnancy, but only 21% to 43% of sexual assault victims who need emergency contraception actually receive it (Amey & Bishai, 2002;Campbell, 2005Campbell, , 2006Campbell & Bybee, 1997;. To date, no studies have found systematic differences in the provision of emergency contraception as a function of victim or assault characteristics, but hospitals affiliated with the Catholic church are significantly less likely to provide emergency contraception (Campbell & Bybee, 1997;Smugar, Spina, & Merz, 2000).…”
Section: Victims' Help-seeking Experiencesmentioning
confidence: 99%